Detorsion Plus Tunica Vaginalis Flap Coverage in the Management of Ischemic Testis Following Torsion: Experience in Dhaka Shishu (Children) Hospital (Dhaka Shishu (Children) Hospital Journal, 2020)
Background: Testicular torsion leads to devastating consequences in young boys, about 42% undergo an Orchiectomy resulting in reduced fertility, testicular hormonal dysfunction and psychological trauma.Objective: The aim was to evaluate the testicular salvage rate after detorsion plus tunica albuginea incision with tunica vaginalis flap coverage with orchiopexy.Methods: This was an observational study conducted from January 2016 to December 2017. Data were collected from operation theater and surgery ward register. Data were analyzed using SPSS version 20 statistical software. Continuous data were presented as mean ± SD and categorical data were presented as percentage. Results: Total numbers of patients were 15. Most of the patients presented after 24 hours. Rate of atrophy of testis after orchiopexy was higher in patients presented after 24 hours. Only 4 patients had recognizable testicular atrophy. Surgical site infection was not present in this study. Conclusion: Tunica albuginea incision with tunica vaginalis flap coverage after detorsion with orchiopexy provides more salvage rate in the management of ischemic testis following torsion.DS (Child) H J 2019; 35(2) : 141-144